2023
DOI: 10.3389/fnagi.2023.1103278
|View full text |Cite
|
Sign up to set email alerts
|

High plasma complement C4 levels as a novel predictor of clinical outcome in intracerebral hemorrhage

Abstract: ObjectiveThe complement cascade is activated and contributes to the brain injury after intracerebral hemorrhage (ICH). Complement component 4 (C4), an important component of complement cascade, has been associated with severity of neurological impairment that occurs during ICH. However, the correlation of plasma complement C4 levels with hemorrhagic severity and clinical outcome in ICH patients has not been reported.Materials and methodsThis study is a monocentric, real-world, cohort study. In this study, we m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…The inclusion and exclusion criteria have been previously described. 25 Peripheral blood samples were centrifuged at 3000 g for 10 min, separated and immediately preserved at −80°C for subsequent analysis. Written informed consent was obtained from the patients or their relatives and the control individuals, and the study was approved by the Medical Ethics Committee of the Affiliated Hospital of Jiujiang University (Grant No.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The inclusion and exclusion criteria have been previously described. 25 Peripheral blood samples were centrifuged at 3000 g for 10 min, separated and immediately preserved at −80°C for subsequent analysis. Written informed consent was obtained from the patients or their relatives and the control individuals, and the study was approved by the Medical Ethics Committee of the Affiliated Hospital of Jiujiang University (Grant No.…”
Section: Methodsmentioning
confidence: 99%
“…The matched healthy controls were selected from patients that visited our medical examination center between January 2022 and May 2022. The inclusion and exclusion criteria have been previously described 25 . Peripheral blood samples were centrifuged at 3000 g for 10 min, separated and immediately preserved at −80°C for subsequent analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Level of plasma complement C4 was determined by turbidimetric measurements using complement C4 assay kit (No. 20230712, Kehua Bio-engineering Co., Ltd., Shanghai, China) ( 15 ). According to the manufacturer’s instructions, the lower C4 quantification limit was 0.16 g/L.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, plasma C4 levels are significantly elevated and are associated with clinical outcomes in patients with hemorrhagic stroke. 82 More importantly, C4 is critical for synaptic pruning, and variations in C4 induce excessive neuronal complement deposition and contribute to increased microglial synapse uptake in cocultured human iPSC-derived neurons and microglia. 83 Two studies involving mouse models also revealed that overexpression of the schizophrenia-associated gene C4 promotes excessive synaptic loss and behavioral changes through microglial synaptic engulfment.…”
Section: Complement Systemmentioning
confidence: 99%
“…Normobaric hyperoxia therapy exerts neuroprotective effects by reducing C3‐mediated synaptic pruning in ICH patients and in a collagenase‐induced mouse model. In addition, plasma C4 levels are significantly elevated and are associated with clinical outcomes in patients with hemorrhagic stroke 82 . More importantly, C4 is critical for synaptic pruning, and variations in C4 induce excessive neuronal complement deposition and contribute to increased microglial synapse uptake in cocultured human iPSC‐derived neurons and microglia 83 .…”
Section: Synapse‐related Signaling Pathways In Strokementioning
confidence: 99%